Performance assessment of four cluster interconnects on identical hardware: hints for cluster builders. (2nd May 2007) - Pourreza, H.; Eskicioglu, M.R.; Graham, P.C.J.
The growing popularity of cluster computing makes it important to understand the performance potential of various interconnects. In this paper, we present the results of a performance analysis of multiple cluster interconnects for various applications running on identical nodes. Timing runs for the NAS and Pallas benchmarks as well as some real world parallel applications running on first and second generation Myrinet, SCI, and fast and gigabit Ethernet were made and the results are reported. These results are particularly valuable for computational scientists who are now building their own clusters but who sometimes have limited technical expertise concerning available cluster interconnects.